2016
DOI: 10.1016/j.colsurfb.2016.01.055
|View full text |Cite
|
Sign up to set email alerts
|

Ionisation effects on the permeation of pharmaceutical compounds through silicone membrane

Abstract: 8Silicone membrane is frequently used as an in vitro skin mimic whereby experiments 9 incorporate a range of buffered media which may vary in pH. As a consequence of such 10 variability in pH there is a corresponding variability in the degree of ionisation which in turn, 11 could influence permeation through the mainly hydrophobic-rich membrane structure. This 12 study reports the effect of pH on the permeation of five model compounds (benzoic acid, 13 benzotriazole, ibuprofen, ketoprofen and lidocaine). For t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…The formation of surfactant micelles creates a hydrophobic core which contains the hydrophobic regions of surfactant and it is known that the hydrophobic core of micelles can strongly interact with hydrophobic molecules and entrap them inside the core [26]. A similar mechanism can be observed in this study where ibuprofen, with a log P value of 3.6 [11], strongly interacted with the hydrophobic core of CHAPS micelles and became trapped inside them thus reducing the number of ibuprofen molecules available to cross through PDMS membrane. Consequently, there would be a reduction in ibuprofen permeation.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…The formation of surfactant micelles creates a hydrophobic core which contains the hydrophobic regions of surfactant and it is known that the hydrophobic core of micelles can strongly interact with hydrophobic molecules and entrap them inside the core [26]. A similar mechanism can be observed in this study where ibuprofen, with a log P value of 3.6 [11], strongly interacted with the hydrophobic core of CHAPS micelles and became trapped inside them thus reducing the number of ibuprofen molecules available to cross through PDMS membrane. Consequently, there would be a reduction in ibuprofen permeation.…”
Section: Resultssupporting
confidence: 82%
“…However, as PDMS is a very simplified model of skin it has the advantage of significantly increasing the level of reproducibility in data acquired yet has the disadvantage of potentially behaving differently to skin under certain conditions. Several factors have already been found to effect permeation including ionisation (as a result of pH) [11], membrane thickness [12] and solvent selection (i.e. donor and receptor solution composition) [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been known for years that the permeability of ionizable compounds depends on the pH of the donor solution, attributed to the slower rate of permeation of ionic species compared to the corresponding neutral species (Roy and Flynn, 1990;Swarbrick et al, 1984;Waters and Bhuiyan, 2016). For instance, Waters and Bhuiyan (2016) recently reported that as an in vitro skin mimic, silicone membrane encouraged permeation of the more unionized forms of pharmaceutical compounds rather than the ionized forms. However, the above reviews completely ignore the possibility of ionization and associated factors such as the dependence of permeation on pH for ionizable compounds, and our previous study represents the only attempt to include ionized species in a model for skin permeation (Zhang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Various kinds of empirical and mathematical models for the correlation and prediction of human skin permeability, as log Kp, have been reported (Baba et al, 2015;Mitragotri, 2003), and there have been a number of reviews of these models (Chen et al, 2013;Geinoz et al, 2004;Mitragotri et al, 2011;Moss et al, 2011;Neely et al, 2009). It has been known for years that the permeability of ionizable compounds depends on the pH of the donor solution, attributed to the slower rate of permeation of ionic species compared to the corresponding neutral species (Roy and Flynn, 1990;Swarbrick et al, 1984;Waters and Bhuiyan, 2016). For instance, Waters and Bhuiyan (2016) recently reported that as an in vitro skin mimic, silicone membrane encouraged permeation of the more unionized forms of pharmaceutical compounds rather than the ionized forms.…”
Section: Introductionmentioning
confidence: 99%